PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR - Nita Fazrina Anggraini; Nicken Destriana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to obtain empirical evidence regarding the effect of factors on tax avoidance measured by Cash Effective Tax Rate (CETR). The independent variables used are company size, audit committee, leverage, sales growth, institutional ownership, and return on assets. The research sample that met the criteria is 60 companies thus there were 180 data listed on Indonesia Stock Exchange, during the 2018-2020 period. The method of sampling is using the purposive sampling method and this study uses multiple linear regression analysis to test the hypothesis. The result of this study indicates that there is only sales growth has negative effects CETR. The lower the CETR value, the more tax avoidance increases, the higher the sales growth in the company, the greater the profit obtained by the company, the company that gets a large profit, the tax payment will also be high. Thus, the company tries to manage its tax burden by making tax savings.